Protocol for a qualitative study exploring the roles of 'Diffusion Fellows' in bridging the research to practice gap in the Nottinghamshire, Derbyshire and Lincolnshire Collaboration for Leadership in Applied Health Research and Care (CLAHRC-NDL). Issue 1 (21st January 2012) - Rowley, Emma
Abstract : Introduction: Evidence produced by researchers is not comprehensibly used in practice. National Institute for Health Research Collaboration for Leadership in Applied Health Research and Care for Nottinghamshire, Derbyshire and Lincolnshire's strategy for closing the research to practice gap relies on the use of 'Diffusion Fellows' (DFs). DFs are seconded from the local healthcare economy to act as champions for change, translating and disseminating knowledge from practice into the research studies and vice versa, taking the knowledge developed by academics back into their own practice environments. This paper outlines the rationale and design of a qualitative evaluation study of the DF role. Methods and analysis: The evaluation responds to the research question: what are the barriers and facilitators to DFs acting as knowledge brokers and boundary spanners? Interviews will be carried out annually with DFs, the research team they work with and their line managers in the employing organisations. Interviews with DFs will be supplemented with a creative mapping component, offering them the opportunity to construct a 3D model to creatively illustrate some of the barriers precluding them from successfully carrying out their role. This method is popular for problem solving and is valuable for both introducing an issue that might be difficult to initially verbalise and to reflect upon experiences. Ethics and dissemination: DFs have an important role within the CLAHRC and are central to our implementation and knowledge mobilisation strategies. It is important to understand as much about their activities as possible in order for the CLAHRC to support the DFs in the most appropriate way. Dissemination will occur through presentations and publications in order that learning from the use of DFs can be shared as widely as possible. The study has received ethical approval from Nottingham 2 Research Ethics Committee and has all appropriate NHS governance clearances.